Perioperative systemic therapies for non-small-cell lung cancer: Recent advances and future perspectives - Lampridis, Savvas; Scarci, Marco (Frontiers in Surgery, 2023)
The mainstay of treatment for early-stage non-small-cell lung cancer (NSCLC) is surgical resection. Traditionally, chemotherapy has been used perioperatively in locally extensive disease to improve the oncologic outcomes of surgery, with a 5-year absolute survival benefit of approximately 5%. In recent years, immunotherapy and molecular targeted therapy have shown excellent results in the treatment of locoregionally advanced and metastatic NSCLC, replacing chemotherapy as first-line treatment in certain cases. Consequently, researchers have been increasingly investigating the use of immunotherapy or targeted therapy in combination with surgery for the treatment of early-stage disease. This growing research interest has resulted in several published and ongoing studies of various size and design. In this mini review, we provide a succinct and up-to-date overview of recently published, phase 3 randomized clinical trials on adjuvant and neoadjuvant immunotherapy or targeted therapy for NSCLC. We subsequently discuss some important unresolved clinical issues, including the optimal duration of treatment, scheduling with respect to surgery, and potential combinations of different systemic therapies. Finally, we reference large, randomized, phase 3 studies that are currently in progress and may give answers to those and other clinical questions.